Քաղաքական-եկեղեցական իրադրությունը Բյուզանդիայում VII դարի առաջին կեսին. հայ և բյուզանդական եկեղեցիների միության փորձը - Կարինե Մելիքյան (ՀՀ ԳԱԱ հրատ.)
В VII в. в Византийской империи монофизиты имели явное преимущество перед xалкедонитами. Император Геракл (610-641) намеревался объединить всеx монофизитов с византийской церковью благодаря новой формуле–доктрине одной энергии и одной воли, т.е. монотелизм. Вначале доктрина укоренилась среди армян на острове Кипр, которые обосновались там в 577 г. Геракл заключает соглашение с епископом Кипра и таким образом впервые проповедуется доктрина одной воли. В средние века церковная доктрина имела политическое значение, с этой точки зрения очень важна история сношений между армянской и византийской церквами. Геракл использовал монотелизм как политическое средство, стремясь примирить монофизитскую армянскую церковь с византийской. В 633 г. созывается собор в Карине, где католикосом Армении была принята доктрина одной воли. Армянские средневековые источники не дают никакой информации о факте монотелизма, они свидетельствуют, что в соборе в Карине католикос принял теологию Xалкедона. In the 7th century in Byzantine empire the antichalcedonians were far more numerous than the Chalcedonians. Emperor Heracles (610- 641) dreamt that it might be possible to unite all the monophysites with the Byzantine church by a new formula – doctrine of a single energy and a single will, called monothelism. In the island of Cyprus there was a colony of Armenians, that was settled there by Justin II in 577. Heracles entered into an agreement with the bishop of Cyprus and the doctrine of one energy and one will was first taught there. It was before 626. In the Middle ages the doctrine of Church had its political importance and from this point of view is very important the history of relations between the Armenian and the Byzantine churches. Heracles made a political weapon of monothelism and tried to reconcile the monophysitic Church of Armenia with the orthodox Byzantine Church. In 633 was held the synod of Karin, where the Catholicos of Armenia accepted the new doctrine of one will. Armenian medieval sources don’t inform the fact of monothelism, on the contrary, they evidence that the synod of Karin has brought into connection with the doctrine of Chalcedon.
Keywords: History; D History; N Fine Arts; NA Architecture